2014
DOI: 10.1007/s11105-014-0834-x
|View full text |Cite
|
Sign up to set email alerts
|

Prosystemin Overexpression in Tomato Enhances Resistance to Different Biotic Stresses by Activating Genes of Multiple Signaling Pathways

Abstract: Systemin is a signal peptide that promotes the response to wounding and herbivore attack in tomato. This 18-amino acid peptide is released from a larger precursor, prosystemin. To study the role of systemin as a modulator of defense signaling, we generated tomato (Solanum lycopersicum) transgenic plants that overexpress the prosystemin cDNA. We carried out a transcriptomic analysis comparing two different transgenic events with the untransformed control. The Gene Ontology categories of the 503 differentially e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 97 publications
(110 reference statements)
1
81
0
Order By: Relevance
“…These multiple functions appear to be strictly correlated with the IDP nature of LEA that work as a hub interacting with multiple partners . Similarly, the disordered nature of Prosys may promote selective binding of several partners as well as integrate signals from multiple stress agents supporting the hypothesis that Prosys has a biological function other than being an intermediate in the synthesis of Sys. Interestingly, as reported for genes encoding IDPs or disordered domains that originated by duplication and module exchange, Prosys gene is thought to be originated through duplication and elongation events …”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…These multiple functions appear to be strictly correlated with the IDP nature of LEA that work as a hub interacting with multiple partners . Similarly, the disordered nature of Prosys may promote selective binding of several partners as well as integrate signals from multiple stress agents supporting the hypothesis that Prosys has a biological function other than being an intermediate in the synthesis of Sys. Interestingly, as reported for genes encoding IDPs or disordered domains that originated by duplication and module exchange, Prosys gene is thought to be originated through duplication and elongation events …”
Section: Discussionmentioning
confidence: 84%
“…In tomato, these events are triggered by a peptide hormone named Systemin (Sys) . The signaling molecule is an octadecapeptide intensely investigated over the years which, upon wounding, is released from the C‐terminal region of a larger pro‐hormone of 200 amino acids called Prosystemin (Prosys) by means of a molecular mechanism still unknown …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, differences between MZ119 and the two PRO8 lines were present only for the GST gene. Pin II was overexpressed in both types of transgenic lines, although at a level that is much lower than in tomato plants overexpressing the prosystemin (Coppola et al 2015). The relative quantification of the expression level of tobacco hydroxyproline-rich glycopeptides HypSys I and II showed an overexpression in both types of transgenic lines.…”
Section: Effects On Endogenous Gene Expressionmentioning
confidence: 89%
“…This eighteenth-amino-acid-long molecule was isolated from tomato leaves, where it is synthesized as a protein precursor-prosystemin (Coppola et al 2015). Grafting experiments showed that, in tomato plants containing prosystemin transgene (transformed rootstock), a systemic signal responsible for production of high content of proteinase inhibitor in undamaged leaves (nontransformed scion) was present (McGurl et al 1994).…”
Section: Modifications Of Expression Of Genes Encoding Various Proteimentioning
confidence: 99%